A INEFICÁCIA DAS MEDIDAS PROTETIVAS NO ÂMBITO DA VIOLÊNCIA CONTRA A MULHER (REMUNOM, 2024)
This paper examines Law 11.340/2006, known as the Maria da Penha Law, focusing on its protective measures and effectiveness. The objective is to highlight the persistent issue of domestic violence against women in Brazil and evaluate whether legal measures are effective in protecting victims. It begins with an overview of domestic violence in the country, detailing the types of violence described in the law and the emergency protective measures provided. The literature review covers the historical origins of domestic violence and the evolution of legal measures to combat it. Field research reveals shortcomings in the application of the measures, underscoring the need for review and improvement of the law to ensure greater protection and effectiveness. The conclusion indicates that, despite progress, the Maria da Penha Law faces significant challenges, particularly related to implementation and institutional support, which compromise its effectiveness in protecting women.